2017
DOI: 10.1007/s00604-017-2603-7
|View full text |Cite
|
Sign up to set email alerts
|

Detection of glutathione based on MnO2 nanosheet-gated mesoporous silica nanoparticles and target induced release of glucose measured with a portable glucose meter

Abstract: The authors describe a novel method for the determination of glutathione (GSH). Detection is based on target induced release of glucose from MnO nanosheet-gated aminated mesoporous silica nanoparticles (MSNs). In detail, glucose is loaded into the pores of MSNs. Negatively charged MnO nanosheets are assembled on the MSNs through electrostatic interactions. The nanosheets are reduced by GSH, and this results in the release of glucose which is quantified by using a commercial electrochemical glucose meter. GSH c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Subsequently, 100 mL of 2 mM RB was dispersed into the above solution, and the resulting mixture was then gently shaken for 16 h at room temperature, the RB molecules were diffused into the pores of the amine-modified AuNRs@SiO 2 . 26,66 MnO 2 nanosheets were synthesized as reported method from reference.66,67 In a 50 mL round-bottom flask, 5 mL of 0.3 M MnCl 2 aqueous solution was mixed with 10 mL of 0.6 M tetramethylammonium hydroxide aqueous solution (3 wt% H 2 O 2 ) for 15 s. After stirring vigorously for 12 h at room temperature, the solution was filtered through a 0.45 mm membrane, washed several times with alternating ultrapure water and methanol, and dried at 50 1C. The product was dispersed in water, and the resulting suspension was treated ultrasonically for 10 h to obtain a brown colloid.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, 100 mL of 2 mM RB was dispersed into the above solution, and the resulting mixture was then gently shaken for 16 h at room temperature, the RB molecules were diffused into the pores of the amine-modified AuNRs@SiO 2 . 26,66 MnO 2 nanosheets were synthesized as reported method from reference.66,67 In a 50 mL round-bottom flask, 5 mL of 0.3 M MnCl 2 aqueous solution was mixed with 10 mL of 0.6 M tetramethylammonium hydroxide aqueous solution (3 wt% H 2 O 2 ) for 15 s. After stirring vigorously for 12 h at room temperature, the solution was filtered through a 0.45 mm membrane, washed several times with alternating ultrapure water and methanol, and dried at 50 1C. The product was dispersed in water, and the resulting suspension was treated ultrasonically for 10 h to obtain a brown colloid.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, the particle size of MSNs can be controlled between 50 and 300 nm; the outer surface and inner pore surface of MSNs are easy to be functionalized, and the volume and release behavior of cargos can be better controlled by surface functionalization. Furthermore, studies have proved the exceptional biocompatibility and low cytotoxicity of MSNs. , The large specific surface area of MSNs provides sufficient space sites and makes it possible to load large numbers of cargos by different gates and diverse design strategies . MSNs are promising candidates for loading a wide range of substances, which has attracted significant attention in developing “turn-off–on” sensing platforms.…”
Section: Introductionmentioning
confidence: 99%
“…28,29 The large specific surface area of MSNs provides sufficient space sites and makes it possible to load large numbers of cargos by different gates and diverse design strategies. 30 MSNs are promising candidates for loading a wide range of substances, which has attracted significant attention in developing "turn-off−on" sensing platforms. Tang et al have designed a novel fluorescence immunoassay method based on target-induced cargo release from protein-gated carbohydrate-functionalized magnetic MSNs and successfully realized the detection of aflatoxin.…”
Section: Introductionmentioning
confidence: 99%
“…Silica-based nanomaterials are also used in peptides and proteins’ detection. That, F. Qu et al [ 74 ] reported the use of mesoporous silica nanoparticles gated with a MnO 2 nanosheet for detecting glutation (GHS). Aminated mesoporous silica nanoparticles were loaded with glucose, and then the pores were caped with negatively charged MnO 2 nanosheets through electrostatic interactions.…”
Section: Detection Studiesmentioning
confidence: 99%